(untitled) (Clinics, 2022)
Objectives: Abnormal expression of long non-coding RNAs (lncRNAs) plays a prominent role in glioma progression. However, the biological function and mechanism of lncRNA DLGAP1 antisense RNA 1 (DLGAP1-AS1) in gliomas are still unknown. Methods: The authors assessed DLGAP1-AS1 and miR-628-5p expression in glioma tissues and cell lines using quantitative real-time polymerase chain reaction (qRT-PCR) and evaluated their effects on glioma cell proliferation, migration, invasion, and epithelial-mesenchymal transition (EMT) using the cell counting kit-8 (CCK-8) assay, 5-Ethynyl-2′-deoxyuridine (EdU) assay, Transwell assay, and western blot, respectively. The expression of DEAD-box helicase 59 (DDX59) was quantified using western blotting, and a dual-luciferase reporter gene assay was performed to detect the interaction between DLGAP1-AS1 and miR-628-5p. Results: The authors observed increased DLGAP1-AS1 expression in glioma tissues and cell lines with higher WHO grades and shorter survival time. DLGAP1-AS1 promoted the proliferation, migration, invasion, and EMT of glioma cells, while miR-628-5p counteracted these effects. The authors identified DLGAP1-AS1 as a molecular sponge of miR-628-5p in glioma cells as the biological functions of DLGAP1-AS1 are partially mediated via miR-628-5p. In addition, DLGAP1-AS1 upregulated DDX59 expression by inhibiting miR-628-5p expression. Conclusion: The DLGAP1-AS1/miR-628-5p/DDX59 axis regulates glioma progression.